Widespread Dominance of Kinetoplastids and Unexpected Presence of Diplonemids in Deep Freshwater Lakes - Mukherjee, Indranil; Hodoki, Yoshikuni; Okazaki, Yusuke; Fujinaga, Shohei; Ohbayashi, Kako; Nakano, Shin-ichi (Frontiers in Microbiology, 2019)
Kinetoplastid flagellates are generally abundant in the deep sea and recently they were even found to be dominant in the hypolimnion of a deep freshwater lake. Therefore, to understand the distribution of kinetoplastids in deep freshwater lakes, we have collected vertical samples from five lakes in Japan. The abundance of kinetoplastids was enumerated by Catalyzed Reporter Deposition-Fluorescence in situ Hybridization, and the diversity was determined by 18S amplicon sequencing using universal eukaryote and kinetoplastid-specific primers. Kinetoplastids were abundant in the deep waters of all the lakes, contributing up to 53.6% of total eukaryotes. Despite this significant contribution, kinetoplastids remain undetected by amplicon sequencing using universal primers that are widely used in eukaryotic diversity studies. However, they were detected with specific primers, and the communities were characterized by both ubiquitous and lake-specific unique OTUs. Oligotyping of a ubiquitous and dominant OTU revealed the presence of lake-specific sequence types (oligotypes). Remarkably, we also detected diplonemids (a sister group of kinetoplastids and considered to be specific in the marine habitat) using kinetoplastid-specific primers, showing their presence in freshwaters. Underestimation of kinetoplastids and diplonemids using universal primers indicates that euglenozoan flagellates are overlooked in diversity studies worldwide. The present study highlighted the importance of kinetoplastids in the hypolimnion of deep lakes, thereby indicating their role in material cycling in deep waters.